Predictors of long-term mortality after first-ever stroke - Hossein Novbakht; Seyed Morteza Shamshirgaran; Parvin Sarbakhsh; Darioush Savadi-Oskouei; Mohammad Marandi Yazdchi; Zohreh Ghorbani (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND AND OBJECTIVE: Data on the factors affecting long-term mortality following a stroke in Iran are scarce. The current research aimed at investigating the extent of 2-year mortality following a stroke and the factors affecting it in the northwest of Iran. MATERIALS AND METHODS: This prospective cohort study was conducted in Tabriz, Northwest of Iran. Patients with computed tomography/magnetic resonance imaging confirmed the first-ever stroke were included in this study and followed up to 2 years. Clinical examinations, including the severity of the stroke using the modified National Institutes of Health Stroke Scale (mNIHSS), were conducted by a neurologist. The general characteristics, lifestyle factors, and laboratory tests were also completed. To estimate the survival, Kaplan-Meier analysis was used; and for group comparison, the log-rank method was applied. To identify the factors predicting 2-year mortality, semiparametric Cox regression analysis was used. RESULTS: A total of 1036 first-ever stroke patients were included in the present study. The mortality rates of stroke in 6-month, 1-year, and 2-years follow-up periods were 31.6%, 34.5%, and 38%, respectively. The two-year mortality rate was 33.6% in ischemic and 58.7% in hemorrhagic stroke (P < 0.001). In the multivariate Cox model, variables age, type of stroke, diabetes, and severity of the stroke, according to the mNIHSS index, were identified as factors predicting 2-year mortality following the stroke. CONCLUSION: The 2-year mortality following acute stroke was relatively high compared to that of in developed countries. Implementation of secondary prevention is recommended to better management of modifiable predictors of mortality.